1980
DOI: 10.1203/00006450-198004000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Diet on Insulin and Gastric Inhibitory Polypeptide Levels in Obese Children

Abstract: SummaryTo improve understanding of the relationships between gastric inhibitory polypeptide (GIP) and insulin secretion and food intake in obesity, immunoreactive insulin and immunoreactive GIP were measured in 5 obese children during PO glucose tolerance test carried out before and after diet.Before diet, mean insulin levels were normal at fasting and rose after glucose ingestion. The mean fasting immunoreactive GIP level was very high (1235 * U)9 pg/ml) compared to that of 8 healthy adult controls (411 f 44 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…In humans, although less clear, there is likewise evidence for a role of GIP in fat metabolism with the demonstration of GIP receptor expression in adipose tissue (Ahlqvist et al ., ), an association between high body mass index and increased GIP levels (Ahlqvist et al ., ; Calanna et al ., ), and increased adipose tissue blood flow and triacylglycerol deposition following GIP administration in a state of high insulin and high glucose (Asmar et al ., ). Furthermore, obese children decrease their basal and postprandial GIP levels, when put on a low‐calorie diet (Deschamps et al ., ), and healthy young men increase their fasting GIP levels, when put on a high‐fat diet (Brøns et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, although less clear, there is likewise evidence for a role of GIP in fat metabolism with the demonstration of GIP receptor expression in adipose tissue (Ahlqvist et al ., ), an association between high body mass index and increased GIP levels (Ahlqvist et al ., ; Calanna et al ., ), and increased adipose tissue blood flow and triacylglycerol deposition following GIP administration in a state of high insulin and high glucose (Asmar et al ., ). Furthermore, obese children decrease their basal and postprandial GIP levels, when put on a low‐calorie diet (Deschamps et al ., ), and healthy young men increase their fasting GIP levels, when put on a high‐fat diet (Brøns et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Deschamps et al . reported a decrease in fasting GIP levels after a dietary intervention in five obese children. In contrast, Reinehr and colleagues have shown that PP levels increase with significant diet‐induced weight loss (BMI z ‐score decrease ≥0.5) but are unchanged in weight stable obese adolescents .…”
Section: Discussionmentioning
confidence: 94%
“…A direct relationship between increased GIP and overeating was demonstrated long ago. Eating less for a few months can reduce both basal and postprandial levels of GIP (Deschamps et al 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in obese and diabetic patients present high GIP (Vilsboll et al 2003) (mainly a proximal gut product). If they loose weight on a diet, GIP falls (Deschamps et al 1980). GIP is obesogenic and insulinotropic (contributing to hyperinsulinemia) (Miyawaki et al 2002), and the therapeutic blockage of GIP has been shown to be beneficial in MS patients (Irwin and Flatt 2009;Montgomery et al 2010).…”
Section: The Gut Imbalance Theorymentioning
confidence: 99%